Pengaruh Motivasi, Kedisiplinan dan Gaya Kepemimpinan Terhadap Kinerja Tenaga Pendidik SMKN 1 Rembang - Moch. Irfan Arya Wardana; Damayanti Damayanti (Departement of Mathematics Education, 2024)
This study aims to investigate the influence of Motivation, Discipline, and Leadership Style on the Performance of Teachers at SMK Negeri 1 Rembang. The research was conducted by analyzing the relationship between these three independent variables and teacher performance as the dependent variable. Data were collected through surveys conducted among teachers at SMK Negeri 1 Rembang. The analysis results indicate that Motivation, Discipline, and Leadership Style have a significant positive influence on teacher performance at SMK Negeri 1 Rembang. These findings underscore the importance of addressing these aspects in improving teacher performance within the school environment. The implications of this research highlight the need for effective management related to motivation, discipline, and leadership style in enhancing teacher performance at SMK Negeri 1 Rembang. Further research could explore other factors that may also affect teacher performance and develop more specific strategies to improve the quality of education at the school.